Workshop Kreasi Konten Media Sosial Untuk Promosi Kesehatan Di RSUD Achmad Darwis Kabupaten Limapuluh Kota - Rahmat Eka Putra; Alhapen Ruslin Chandra; Sepri Neswardi; Nurhayati; Imelda M Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
The social media content creation workshop for health promotion involves non-commercial partners of Achmad Darwis Hospital, Limapuluh Kota Regency, West Sumatra. Along with the development of information technology and digitalization, partners are increasingly aware of the need to optimize social media management as a key element in building the image of the hospital and improving the quality of services to the community. However, existing human resources do not yet have specific expertise in creating effective content for social media. Therefore, it is necessary to hold a social media content creation workshop in order to improve the skills of the Achmad Darwis Hospital health promotion (Promkes) team. A total of 20 participants were involved in this activity. The activity was carried out in stages, starting with lectures, practice, and finally discussions. Quantitatively, an evaluation was carried out by conducting a written test on the material that had been given. The results showed that there was an increase in participants' knowledge in making videos by comparing the test results before and after training. The results obtained from this activity contribute to improving the ability of the Achmad Darwis Hospital Health Promotion team to create content for social media that can improve the image of the hospital and optimize services for the community. It is hoped that this activity can improve the knowledge, skills, and abilities (KSA) of the Achmad Darwis Hospital health promotion team in developing content for social media. It is recommended for health promotion teams to continue to hone their skills in creating health content in order to optimize hospital services and performance.